Persepsi Guru dan Siswa terhadap Pembelajaran Tatap Muka (PTM) Terbatas pada Masa Pandemi Covid-19 Sekolah Dasar di Pinggiran DAS Sungai Kahayan SDN-1 Desa Hanua, Kabupaten Pulang Pisau - Revianti Coendraad; Whendy Trissan; Topan Eka Putra (Jurnal Ilmiah Kanderang Tingang, 2022)
Many students feel bored studying online due to the impact of the Covid 19 pandemic since March 2020 because they cannot interact directly with their teachers and friends. On March 30, 2021, 4 Ministerial Joint Decrees (SKB) were issued, namely the Minister of Education and Culture, Minister of Religion, Minister of Health and Minister of Home Affairs Number 03/KB/2021, Number 384 of 2021, Number HK.01.08/MENKES/4242/ 2021, Number 440-717 of 2021 concerning Guidelines for Organizing Learning During the 2019 Coronavirus Disease (COVID-19) Pandemic. Through this joint decision, the government encourages limited face-to-face learning (PTM) acceleration while still implementing strict health protocols. Since the publication of the Joint Decree of 4 ministers concerning Guidelines for Organizing Learning During the 2019 Corona Virus Disease (COVID-19) Pandemic, many schools have conducted face-to-face learning. A limited face-to-face learning process has been carried out from mid-July 2021 until now. Limited Face-to-Face Learning (PTM) was carried out in one of the elementary schools at SDN-1 in Hanua Village, which is located on the outskirts of the Kahayan River watershed, Pulang Pisau Regency. This school as a whole has 8 teachers and 33 students, which in the implementation of limited PTM are scheduled from the school. The type of research used is a descriptive qualitative research approach. The place where the research was carried out at the research subject was a source for obtaining information and information from the research desired in this study. The subjects were teachers and high school students at SDN-1 Hanua Village, Pulang Pisau Regency. From the results of observations and interviews with teachers and students, it was found that according to teachers' perceptions they strongly agreed with limited PTM during the pandemic because it was more effective in using direct learning methods and resources to students so that it was easier to coordinate learning in class than online because it is indeed a network in the village not smooth so that it becomes an obstacle to online meetings. Meanwhile, according to student perceptions, they stated that students were very happy with limited face-to-face meetings during the pandemic because they could interact with their friends and felt comfortable studying at school, conducting learning in question and answer classes and understanding better the lessons given by the teacher in class.